Draft 7th Five Year Plan 1985-90 and Annual Plan 1985-86 Vol. XI Ladakh Sub Plan Jammu and Kashmir Government - Planning Commission (Planning Commission, 1984)
On account of erratic and scanty precipitation cold grid deserted conditioning prevalent in the district. Dry land cultivation is as such not possible and the entire cultivable area comprising 10280 hectares subsist on assured irrigation. The whole cultivable area is single cropped with only marginal areas under double crop. The department of Agriculture's primary objective is to improve, the production of cereals, vegetables, fodder and horticultural crops by adoption of intensive measures of cultivation, distribution of improved varieties of seeds and chemical fertilizers and adoption of plant protection resources. Qualities of existing fruit trees are sought to be improved under the massive Programme for top working and budding with improved cultivars.
Jammu and Kashmir Government, Planning and Development Department